High-pressure structures of yttrium hydrides. (14th July 2017) - Liu, Lu-Lu; Sun, Hui-Juan; Wang, C Z; Lu, Wen-Cai
Abstract: In this work, the crystal structures of YH3 and YH4 at high pressure (100–250 GPa) have been explored using a genetic algorithm combined with first-principles calculations. New structures of YH3 with space group symmetries of P21/m and I4/mmm were predicted. The electronic structures and the phonon dispersion properties of various YH3 and YH4 structures at different temperatures and pressures were investigated. Among YH3 phases, the P21/m structure of YH3 was found to have a relatively high superconducting transformation temperature T c of 19 K at 120 GPa, which is reduced to 9 K at 200 GPa. Other YH3 structures have much lower T c s. Compared with YH3, the T c of the YH4 compound is much higher, i.e. 94 K at 120 GPa and 55 K at 200 GPa.